Hypertension across the lifespan: Adults. Issue 3 (May 2021) - Bruce, Kellie; Hilliard, Tara C.; Esquibel, Karen A.; Mello, Inola; Moore, Amy
Abstract : Learn how to identify at-risk patients to facilitate timely intervention and promote positive outcomes. Abstract : Learn how to identify at-risk patients to facilitate timely intervention and promote positive outcomes.